2014
DOI: 10.1016/j.jadohealth.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Media and the Internet on Vaccine Adverse Event Reporting: A Case Study of Human Papillomavirus Vaccination

Abstract: Purpose This study aimed to determine the temporal association of print media coverage and Internet search activity with adverse events reports associated with the human papillomavirus vaccine Gardasil® (HPV4) and the meningitis vaccine Menactra® (MNQ) among U.S. adolescents. Methods We used moderated linear regression to test the relationships between print media reports in top circulating newspapers, Internet search activity, and reports to the Vaccine Adverse Event Reporting System (VAERS) for HPV4 and MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
1
33
0
4
Order By: Relevance
“…In our population internet appears not to be a commonly used source of information in contrast to another Greek study of medical and nursing students of older age [36]. It is reported that comprehensive information is not adequately covered in the internet [37] and vaccination risks are exaggerated [38].…”
Section: Discussionmentioning
confidence: 63%
“…In our population internet appears not to be a commonly used source of information in contrast to another Greek study of medical and nursing students of older age [36]. It is reported that comprehensive information is not adequately covered in the internet [37] and vaccination risks are exaggerated [38].…”
Section: Discussionmentioning
confidence: 63%
“…is the vector of 13 Some empirical research has focused on modelling the ways information is divulged via the Internet, and the speed at which this happens in matters far removed from the question of uncertainty: see, for example, Eberth et al (2014).…”
Section: -The Methodological Frameworkmentioning
confidence: 99%
“…Há que se considerar que, em campanhas de vacinação e introdução de novas vacinas, as informações veiculadas na mídia podem contribuir para que a população fique mais atenta à importância da vacinação, com novos conhecimentos e busque um serviço de saúde diante de um EAPV, o que possivelmente, aumentará a notificação de eventos adversos (Eberth et al, 2014;Luna, Gattás, Campos, 2014).…”
Section: Erro De Imunização Com Evento Adverso No Brasil E No Paranáunclassified
“…Então, diante de um erro sem danos, optam por se calar e não notificar (Bohomol, Ramos, 2007;Leape, 2007;Harada, 2006) Outro fator que pode ter contribuído para esta elevação foi a influência da mídia e da internet sobre a população, alertando-a para as campanhas de vacinação, bem como, cuidados com a sua segurança (Eberth et al, 2014;Luna, Gattás, Campos, 2014).…”
Section: Erro De Imunização Sem Evento Adverso No Paranáunclassified
See 1 more Smart Citation